Design and Development of Efficient IOT Based Machine Learning Model to Monitor Shrimp Aquaculture - A V L N Sujith , Vadetay Saraswathi Bai, T Venkata Naga Jayudu, Mallarapu Harish (International Journal of Advanced Science and Technology, 2020)
The study mainly focuses on the development of an IoT model which is integrated with the submersible cameras in the context of monitoring the habitation of shrimps. Shrimp culture is considered to a most beneficial business in different parts of India. It is also well known that, the monitoring and habitation of the shrimps is the most challenging aspect as they are easily prone to different pandemic viruses that are easily contagious to the rest of the shrimps in the shrimp ponds. In this study, a computer vision based machine learning algorithm is employed in the process of automating the habitation of the shrimp such that this mechanism will help in the early diagnosis of infected shrimps that will help us to restrict the pandemic.